Pipe Dream Play Still - Sam S. Shubert Theater:::Creator::::::::::::
Fauna (Helen Traubel) singing The Bum's Opera in the musical based off John Steinbeck's 'Sweet Thursday.' This show closed after 245 performances at the Sam S. Shubert Theatre.Digital copy only. No hard copy.